EKSISTENSI AGAMA HINDU KAHARINGAN DI KOTA PALANGKARAYA KALIMANTAN TENGAH - Wakhid Sugiyarto (Harmoni, 2016)
This study aims at understanding the existence of the religion of Kaharingan in the city of Palangkaraya. This is related to the existing clash happening within the adherents of Hinduism which is quite intense involving two camps in Hinduism namely traditional Hinduism and spiritual Hinduism. Several aspects to be explored includes the history and development; the number of followers, organization, figures and symbols, traditions, self-defend medium, and the relationship with other Hindus. The basic argument used is that in Hinduism theology, there is no such a thing as one system of salvation, of theology, of rituals, of offerings and of tradition. In any kind of theology system in either monism, monotheism or panteism, all have the same system of god in Hinduism including Kaharingan. By adopting observation method, literature review and in-depth interview, the author analyzes that followers of Kaharingan are able to survive, regardless of the problem they are facing in Palangkaraya, central Kalimantan. This is due to some reasons as follows: firstly, there is no religious literature in Kaharingan; secondly, the capacity of spiritual leaders is in need of improvement; and thirdly, there is no effort of proselytizing Kaharingan belief that can add the number of followers. This last aspect is crucial as Kaharingan followers are stagnant in number and tend to decline. Besides, Dayak community in central Kalimantan who were previously traditional supporters of Kaharingan have now turned out to be Muslims.